PKM Perencanaan dan Perancangan Bangunan Posyandu Dengan Konsep Low Cost di ORW 09 Kelurahan Tamalanrea, Kota Makassar - Wahyuni, Arinda; Baso, Nur Fadliah (Idea Pengabdian Masyarakat, 2024)
The Posyandu in ORW 09 Tamalanrea subdistrict, is not provided with proper facilities. Until now, ORW 09 has not had a posyandu facilities. Currently, the posyandu operates on the pouch of the ORW 09 Block L head’s house. The leadership of the Rukun Warga in Blok L ORW 09 plans to construct a suitable Posyandu for the residents of 09 BTP Block L with adequate facilities. The leadership of Rukun Warga 09 Blok L intends to build a proper Posyandu for residents of 09 BTP Blok L and has received approval during the 2023 MUSRENBANG by Tamalanrea Subdistrict to fund the construction of the Posyandu in ORW 09. It has also been included in the 2023 budged. However, the budget is limited, with only approximately 50 million allocated by Tamalanrea subdistrict. The leadership of ORW 09 greatly hopes that this construction will be realized in 2023 to make the Posyandu run more effectively. Consequently, the assistance of an architect is needed to plan a low-cost Posyandu in other words, the construction should be costeffective due to limited construction budget. Besides being low cost in terms of construction, the leadership of ORW 09 also expects a low cost design in terms of energy consumption since this building is self-funded public facility. Various issues faced by ORW 09 Tamalanrea Subdistrict, as outline d above, led the PKM proposing team to agree with the partner (ORW 09 Tamalanrea Subdistrict) informulating priority issues that can be addressed according to the expertise of the PKM proposing Team members. Priority issues are categorized asissues related to facilities and infrastructure.